Design and initial operation of multichord soft X-ray detection array on the U-3M torsatron - Dreval, M.B. (Вопросы атомной науки и техники, 2014)
A miniature pinhole camera array for spatially and temporally resolved measurements of soft X-ray emission has been designed and installed in the URAGAN-3M torsatron. Two features of the U-3M: a) very large vacuum vessel; b) a quite high RF noise from the 8-9 MHz plasma heating generators, form a rather difficult for the SXR system design conditions. In order to increase the SXR brightness in 25-50 times the pinhole camera is placed between helical coils near plasma in the “A-A” cross-section. The size of the pinhole and its location relative to the diode array are optimized to cover the whole poloidal cross section and to achieve a good spatial resolution with minimum overlap in nearby channels. Possible misalignments of the SXR system can cause errors in the line of sight impact parameter less than 3⁰ (similar to the SXR channel viewing angle). The maximum of the measured SXR brightness intensity corresponds to the central channel № 11 of the system. The 2.5•10⁷ V/A SXR photodiode photocurrent amplifiers with additional RF noise suppress electronics have been manufactured. The SXR electronics does successfully work in high vacuum conditions near the plasma. Time evolution of the SXR emission profile and its fluctuations are successfully measuring by the designed diagnostics. Миниатюрный датчик для измерения временного поведения и пространственного распределения излучения мягкого рентгена был спроектирован и установлен на торсатроне УРАГАН-3М (У-3М). Две особенности У-3М: а) очень большой вакуумный объём; б) очень большой ВЧ-шум от 8-9 МГц-генераторов, нагревающих плазму, формируют очень сложные условия для проектировки диагностики мягкого рентгена. Для того, чтобы увеличить измеряемую светимость рентгена в 25-50 раз, измеряющая рентген камера обскура помещена между винтовыми проводниками рядом с плазмой в сечении “A-A”. Размер входной щели и её расстояние до набора фотодиодов камеры обскура оптимизированы для покрытия всего полоидального сечения плазмы и получения хорошего пространственного разрешения при минимальном перекрытии соседних каналов. Проведённые оценки показали, что возможные перекосы камеры могут вызвать ошибку в определении прицельного параметра хорды наблюдения меньше, чем величина угла обзора канала мягкого рентгена, в 3⁰. Максимум измеряемой интенсивности светимости мягкого рентгена приходится на центральный канал № 11. Изготовлены усилители фототока чувствительностью 2,5•10⁷ В/А с дополнительной электроникой, подавляющей ВЧ-шум. Электроника успешно работает в условиях высокого вакуума рядом с плазмой. Временная эволюция профиля эмиссии мягкого рентгена и её флуктуаций успешно измеряются разработанной диагностикой. Мініатюрний датчик для вимірювання часового поводження та просторового розподілу випромінювання м'якого рентгена був спроектований і встановлений на торсатроні УРАГАН-3М (У-3М). Дві особливості У-3М: а) дуже великий вакуумний об'єм; б) дуже великий ВЧ-шум від 8-9 МГц-генераторів, що нагрівають плазму, формують дуже складні умови для проектування діагностики м'якого рентгена. Для того, щоб збільшити світність рентгена, що вимірюється, в 25-50 разів, камера обскура поміщена між гвинтовими провідниками поруч з плазмою у перерізі "А-А". Розмір вхідної щілини і її відстань до набору фотодіодів камери обскура оптимізовані для покриття всього полоідального перерізу плазми і отримання доброго просторового розділення при мінімальному перекритті сусідніх каналів. Проведені оцінки показали, що можливі перекоси камери можуть викликати помилку у визначенні прицільного параметра хорди спостереження менше, ніж величина кута огляду каналу м'якого рентгена, в 3⁰. Максимум вимірюваної інтенсивності світності м'якого рентгена припадає на центральний канал № 11. Виготовлені підсилювачі фотоструму чутливістю 2,5•10⁷ В/А з додатковою електронікою, що переважає ВЧ-шум. Електроніка успішно працює в умовах високого вакууму поруч з плазмою. Часова еволюція профілю емісії м'якого рентгена і її флуктуацій успішно вимірюються розробленою діагностикою.